Perberdayaan Masyarakat Desa Melalui Inovasi Ekonomi dan Edukasi Hukum untuk Meningkatkan Kesejahteraan Berkelanjutan - Desvita Laura; Jufri Sani Akbar; Yang Meliana; Rahmadiah Rahmadiah; Yoga Saputra (Nusantara Mengabdi Kepada Negeri, 2025)
The Community Service Program (Kuliah Kerja Nyata / KKN) is a form of higher education’s commitment to applying academic knowledge in real-life settings to empower rural communities sustainably. This KKN program was conducted in Nangka Village, Air Gegas District, Bangka Selatan Regency, focusing on strengthening economic innovation and legal education to improve community welfare. The activities were implemented through a participatory approach consisting of initial observation, collaborative planning with village authorities and target groups, program implementation such as MSME mentoring, digital marketing training, legal awareness sessions, social outreach, and participatory evaluation. The results revealed improvements in local entrepreneurs’ capacity to market their products digitally, enhanced legal awareness among villagers, increased skills and participation of local youth in economic and social activities, and the emergence of sustainable initiatives supported by the village government. In conclusion, integrating economic innovation with legal education through KKN has proven effective in enhancing community welfare and strengthening inclusive and sustainable village empowerment.